Smoke and ashes : a writer's journey through opium's hidden histories - Ghosh, Amitav, 1956- (New Delhi : Harper collins, 2023)
"Amitav Ghosh unravels the impact of the opium trade on global history and in his own family-the climax of a yearslong project"--
Includes bibliographical references.
Keywords: Ghosh, Amitav, -- 1956- -- Travel; Ghosh, Amitav, -- 1956- -- Family; Opium trade -- History; China -- Commerce -- History; India -- Commerce -- History; Great Britain -- Commerce -- History